2019
DOI: 10.1002/anie.201904698
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Cascade Cyclization of Indolyl Homopropargyl Amides: Stereospecific Construction of Bridged Aza‐[n.2.1] Skeletons

Abstract: Catalytic cycloisomerization-initiated cascade cyclizations of terminal alkynes have received tremendous interest, and been widely used in the facile synthesis of adiverse arrayof valuable complex heterocycles.H owever,t hese tandem reactions have been mostly limited to noble-metal catalysis,and are initiated by an exo-cyclization pathway. Reported herein is an unprecedented copper-catalyzed endo-cyclization-initiated tandem reaction of indolyl homopropargyl amides,w here copper catalyzesb oth the hydroaminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 100 publications
0
20
0
Order By: Relevance
“…Further screening of solvents such as toluene and chlorobenzene led to as lightly decreased yield (entries [14][15]. [20] Besides the formation of bridged aza-[3.2.1] skeletons,this copper-catalyzed cascade cyclization was also viable for the construction of other valuable bridged aza-[n.2.1] skeletons. [17] Thus,both the metal catalyst and protecting group of the substrate are the key to achieve the desired cascade cyclization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further screening of solvents such as toluene and chlorobenzene led to as lightly decreased yield (entries [14][15]. [20] Besides the formation of bridged aza-[3.2.1] skeletons,this copper-catalyzed cascade cyclization was also viable for the construction of other valuable bridged aza-[n.2.1] skeletons. [17] Thus,both the metal catalyst and protecting group of the substrate are the key to achieve the desired cascade cyclization.…”
Section: Resultsmentioning
confidence: 99%
“…Initial investigation of N-protecting groups of the amide moiety demonstrated that the reaction proceeded smoothly with different sulfonyl groups to furnish the desired aza-[3.2.1] skeletons 2a-d in 68-84 %yields (entries 1-4), and the Ts-protected homopropargyl amide 1a gave the best result (entry 1). [20] In addition, other heterocycle-tethered homopropargyl amides 7a-c,and even the alkoxy arene-substituted amide 7d were suitable substrates for such ac opper-catalyzed cascade cyclization, delivering the desired aza-[3.2.1] skeletons 8a-d in 56-86 %y ields [Eqs. In addition, amides containing different substituents on the indole ring also underwent smooth cascade cyclization,p roducing the corresponding 2f-n in good to excellent yields (entries [6][7][8][9][10][11][12][13][14], Finally,i tw as found that the reaction also occurred well with (S)-(+ +)-tert-butylsulfinamide-derived 1e' ',a nd thus the other enatiomer, 2e' ', was specifically produced (entry 15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ye and co-workers disclosed the first copper-catalyzed tandem reaction of chiral indolyl homopropargyl amide 67 involving a 5- endo- dig hydroamination and a subsequent Friedel–Crafts alkylation [ 66 ]. This method afforded bridged aza-[ n .2.1]-indole-based tropanes in most examples, but was also extended to indole-fused medium-sized heterocycles 68 ( Scheme 25 ).…”
Section: Methods Using Copper-catalyzed Reactionsmentioning
confidence: 99%
“…This approach was compatible with aliphatic, aryl, and heteroaryl aldehydes, allowing access to various 8-and 9-membered saturated N,N-and N,O-heterocycle 66 products (Scheme 24). Ye and co-workers disclosed the first copper-catalyzed tandem reaction of chiral indolyl homopropargyl amide 67 involving a 5-endo-dig hydroamination and a subsequent Friedel-Crafts alkylation [66]. This method afforded bridged aza-[n.2.1]-indole-based tropanes in most examples, but was also extended to indole-fused medium-sized heterocycles 68 (Scheme 25).…”
Section: Carbon-carbon Bond Formationmentioning
confidence: 99%